Students' Understanding of Boiling Points and Intermolecular Forces - Schmidt, H.; Kaufmann, B.; Treagust, David (The Royal Society of Chemistry, University of Ioannina, 2009)
In introductory chemistry courses students are presented with the model that matter is composed of particles, and that weak forces of attraction exist between them. This model is used to interpret phenomena such as solubility and melting points, and aids in understanding the changes in states of matter as opposed to chemical reactions. We investigated upper secondary school students’ models for intermolecular forces and their abilities to use these for predicting the relative boiling points of organic compounds. Written tests were administered to students in grades 11 to 13 (aged 16 to 19) in Germany. Students’ answers, and especially the reasons they gave for their answers, were analysed. Results indicate students had difficulty predicting the relative boiling points of organic compounds. The most prominent alternative conception was that boiling involves breaking covalent bonds. Results also indicate that students used alternative models for hydrogen bonds, limiting the occurrence of hydrogen bonds to the presence of oxygen and hydrogen atoms, or to dipolar molecules. The results show that the understanding of intermolecular forces in upper secondary school is inadequate, and that teaching should be changed. The items developed in this study could be incorporated into classroom discussions.